The Influence of Personality Traits on Ethical Behavior of Police: The Mediating Effect of Ethical Leadership - Norlida Zakirai Zakaria; Idris Osman; Shereen Noranee (Information Management and Business Review, 2023)
Unethical behavior by police officers continues to garner a lot of attention. Engagement in such conduct will tarnish police reputation as law enforcers who are responsible to protect the welfare of society. Hence, fostering ethical behavior among police officers should be encouraged. However, there is a dearth of in-depth knowledge in existing literature, providing a sufficient explanation contributing to the ethical behavior of police officers. The purpose of this study is to assess the influence of the reciprocal relationship between personal factors and environmental factors on behavioral outcomes. By employing the Social Cognitive Theory (SCT) as an underpinning theory, this present study intends to examine the influences of personal factors, namely personality traits, on the ethical behavior of the police. This study also introduces ethical leadership as a mediating variable to fill the knowledge gap in the existing literature.